Review: Improving quality of life in patients with differentiated thyroid cancer - Pace-Asciak, Pia; Russell, Jonathon O.; Tufano, Ralph P. (Frontiers in Oncology, 2023)
Well differentiated thyroid cancer is a common malignancy diagnosed in young patients. The prognosis tends to be excellent, so years of survivorship is expected with low risk disease. When making treatment decisions, physicians should consider long-term quality of life outcomes when guiding patients. The implications for treating indolent, slow growing tumors are immense and warrant careful consideration for the functioning years ahead. Surgery is the standard of care for most patients, however for a subset of patients, active surveillance is appropriate. For those wishing to treat their cancer in a more active way, novel remote access approaches have emerged to avoid a cervical incision. In the era of “doing less”, options have further expanded to include minimally invasive approaches, such as radiofrequency ablation that avoids an incision, time off work, a general anesthetic, and the possibility of post-treatment hypothyroidism. In this narrative review, we examine the health related quality of life effects that surgery has on patients with thyroid cancer, including some of the newer innovations that have been developed to address patient concerns. We also review the impact that less aggressive treatment has on patient care and overall wellbeing in terms of active surveillance, reduced doses of radioactive iodine (RAI) treatment, or minimally invasive techniques such as radiofrequency ablation (RFA) for low risk thyroid disease.